Investigating culture and its influence on socio-economic development in the Kingdom of Eswatini / Aaron Gwebu and Md Humayun Kabir - Gwebu, Aaron; Kabir, Md Humayun (Faculty of Accountancy, 2019)
In the socio-economic sphere, culture has become one of the influences or determinants of the same. Depending on the living environment, culture has tended to be either a resource or an impediment of socio-economic development (SED). The purpose of this study is to investigate existing cultures influencing SED in light of the prevailing socio-economic situation in the Kingdom of Eswatini. A mixed-method (qualitative and quantitative) approach was used. Traditional leaders, constituency heads and development practitioners were considered as sample data for the study, where stratified sampling technique was employed in order to accommodate the diverse groups. Results of the study indicate that cultural influence is most prevalent in the rural communities, while the adoption of the new national constitution in 2005 brought an insignificant change in the way culture influences SED. From the findings of the study, it was noted that cultural governance, cultural tourism, customs and traditions, gender discrimination and marginalisation of people living with disabilities are the main existing components relating to the area of the central phenomenon. Further findings indicate that culture in the Kingdom is largely epitomised by the existence of the Monarchy authority, as a wide range of norms, beliefs, customs and traditions are entrenched in the core values of same. This infers that the Kingdom of Eswatini is predominated by socio-cultural values, which necessitates a telling influence on SED issues. A major recommendation would be the formulation of constitutionalised legislation with domesticated regulations and policies that will seek to balance the values and systems of culture with those of socio-economic development. The study creates awareness among the citizenry on the existing cultural influence to SED, which is something that could stimulate willingness to change their current mind-set and perceptions about culture and socio-economic development for the better.